Misophonia: A Review of the Literature and Its Implications for the Social Work Profession. - Holohan, Daniel; Marfilius, Kenneth; Smith, Carrie J (Social Work, 2023)
Misophonia is a chronic condition that describes aversion to specific auditory stimuli. Misophonia is characterized by physiological responsivity and negative emotional reactivity. Specific sounds, commonly referred to as "triggers," are often commonplace and sometimes repetitive. They include chewing, coughing, slurping, keyboard tapping, and pen clicking. Common emotional responses include rage, disgust, anxiety, and panic while physical responses include muscle constriction and increased heart rate. This literature review identifies research priorities, limitations, and new directions, examining the implications of misophonia for the social work profession. Misophonia is largely absent from the social work literature. However, the profession is uniquely equipped to understand, screen for, and effectively treat misophonia in direct practice or within interprofessional treatment teams. By conceptualizing misophonia as idiosyncratic and contextual, social workers would enhance the existing body of research by applying an ecological perspective which captures the interaction of individuals and environments in producing human experience. Such an approach would assist clients and clinicians in developing treatment plans that consider the roles of social and physical environments in the development and course of misophonia. A discussion of current limitations within the misophonia literature further emphasizes the need for new perspectives.